Peranan Pemerintah Desa Dalam Mewujudkan Wisata Tani Sebagai Program Inovasi Desa Di Desa Melati II Kecamatan Perbaungan - Audrey, Wika; Lubis, Yurial Arief; Kurniaty, Evi Yunita (Universitas Medan Area, 2024)
The purpose of this study was to determine the role of the village government in realizing farm tourism as a village innovation program in Melati II Village, Perbaungan District. This question is focused by Labolo's (2010:32) work to get an answer using his Ryaas Rasyid role theory. This theory includes 1) the role of government as regulator, 2) the role of government as dynamist, and 3) the role of government as facilitator and mediator. Political theory by Carl J. Friedrick in Suwitri (2008:5-6). Data obtained in the field were collected by primary and secondary data acquisition techniques and analyzed qualitatively. The study concludes that the role of village government of Melati II in realizing agritourism in Panten Cresset through village innovation program is not yet complete. This has been attributed to a role that has not been performed effectively, a lack of enthusiasm in providing direction, guidance and socialization to the community, and an underutilization in managing the assistance provided by the Ministry. Not due to the role of village government in Melati II. Go to a village in the Republic of Indonesia and pay no attention to access to the target. Panten Creset Farm Tour. The obstacle facing the village government of Melati II is the emergence of Covid-19.